Investigating the cloud radiative effect of Arctic cirrus - Marsing, Andreas; Meerkötter, Ralf; Heller, Romy; Kaufmann, Stefan; Jurkat-Witschas, Tina; Krämer, Martina; Rolf, Christian; Voigt, Christiane (Atmospheric Chemistry and Physics, 2023)
The radiative energy budget in the Arctic undergoes a rapid transformation compared to global mean changes. Understanding the role of cirrus in this system is vital, as they interact with short- and long-wave radiation and the presence of cirrus can be decisive as to a net gain or loss of radiative energy in the polar atmosphere. In an effort to derive radiative properties of cirrus in a real scenario in this sensitive region, we use in-situ measurements of ice water content (IWC) performed during the POLSTRACC aircraft campaign in the boreal winter and spring 2015/2016 employing the German research aircraft HALO. A large dataset of IWC measurements of mostly thin cirrus at high northern latitudes was collected in the upper troposphere and also frequently in the lowermost stratosphere. From this dataset we selected vertical profiles that sampled the complete vertical extent of cirrus cloud layers. These profiles exhibit a vertical IWC structure that will be shown to control the instantaneous radiative effect both in the long and short wavelength regimes in the polar winter.